Physical and Mechanical Properties of Edible Film from Porang (Amorphopallus oncophyllus) Flour and Carboxymethylcellulose - P., Sudaryati H.; S., Tri Mulyani; Hansyah, Egha Rodhu (Jurnal Teknologi Pertanian, 2010)
Porang (Amorphophallus onchophyllus) is a shrub and its tuber contains glucomannan that functions as dietray fiber.  Glucomannan is a polysaccharides comprised of galactose, glucose, and mannose.  Glucomannan and carboxymethylcellulose can be used as the raw materials of edible film, however the resulting edible film has low elasticity and the quality is affected by its dryness.  The aims of this reserach were to study the effect of glycerol as plasticizer and drying time on the edible film quality, as well as deterimation the best teratment.  This study used  Completely Randomized Design with two factors: glycerol concentration of 1, 2, and 3%; and drying time at 75C for 3, 3.5, and 4 hours.  The result showed that increasing drying time resulted in decreasing water vapor transmission, oxygen transmission, moisture content, water activity, elongation and thickness of edible film,  Meanwhile, increasing glycerol concentration decreased water vapor transmission, oxygen transmission, and water activity, but increased moisture content, elongation, and thickness of edible film.  The best treatment obtained at glycerol concentration of 3% and drying time of 4 hours.  The resulting edible film had characteristics as followed: moisture content of 25.58%, water vapor transmission of 4.65 g/m²/24 hours, oxygen transmission of 1.38 ml/m²/24jam, Aw of 0.54, elasticity of 65.57 %, and thickness of 0.13 mm.Keywords: porang flour, edible film, glucomannan, carboxymethylcellulose